PENGARUH KUALITAS PRODUK, HARGA, PROMOSI DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO BUDI FROZEN DI BALIKPAPAN - Iskandar, Amir; Taufik, Dwi; Prihandoyo, C (MEDIA RISET EKONOMI [MR.EKO], 2023)
The purpose of this study was The Influence of Product, Price, Promotion and Location on Consumer Purchasing Decisions of Budi Frozen Stores in Balikpapan. To determine This research was conducted at Budi Frozen Stores in Balikpapan, with 144 respondents. This research method uses quantitative methods. Collecting data by distributing questionnaires directly. The data analysis technique used to research is multiple linear analysis by conducting instrument tests, classical assumption tests, and partial hypothesis testing (t-test). The results showed that product, price, location, and promotion variables had a positive and significant effect on purchasing decisions at Budi Frozen Stores in Balikpapan.